Innovative technologies in hypertension control A telemonitored cuff-less blood pressure device - Xufre, Mikael Tomás (2020)
Introduction: Known as the most prevalent cardiovascular risk factor, hypertension, or High Blood Pressure (HBP), affects up to 1.13 billion people worldwide. It is responsible for up to 45% of deaths from cardiovascular disease and 51% of deaths from stroke. It is currently known that one of the reasons is that patients with hypertension are at greater risk of developing atrial fibrillation (AF) and consequent arterial thromboembolism to the cerebral circulation. It has been showed that reducing and maintaining blood pressure (BP) in hypertensive patients at levels considered ideal has a significant impact in reducing associated mortality and morbidity. Thus, the control of hypertension becomes essential. In addition to patient involvement, some technologies have showed potential in improving this control, such as telemonitoring and AF detection algorithms in BP monitoring devices. New devices have attempted to encompass telemonitoring, AF detection and greater ease of use such as smartwatches or other wrist meters with or without a cuff, however, most fail to obtain certification and clinical validation. In this study, a new portable cuff-less BP meter, which includes heart rate measurement, telemonitoring and detection of suspected AF rhythms is evaluated. The measurements are carried out in about 10 seconds at the wrist level and the device has the advantage of being already certified and clinically validated by the European Society of Hypertension. Objective: Evaluate the opinion of a group of patients with hypertension about a new portable and cuffless BP meter (FreeScan®, Maisense) after using it for 1 month through a questionnaire and evaluate the number of recommended measurements performed. Material and methods: Patients being followed up at HBP consultation who had access to a smartphone (necessary for telemonitoring) were invited to participate in the study. A Freescan® device was provided, it was demonstrated how it function and the calibration with a digital BP meter with arm cuff (Rossmax X5®) was made. For followup, participants were asked to take 2 consecutive measurements in the morning before taking medication for HBP and 2 consecutive measurements at the end of the day, preferably before dinner. After the 4 weeks, a meeting was arranged to collect the device and to deliver a questionnaire, in order to assess the participant's opinion on different aspects of the Freescan® device. Results: We obtained a final sample of 20 participants. The mean age was 57.15 (standard deviation (SD) 9.88) years. The average number of days with at least 1 measurement was 23,05 (SD 8,80) corresponding to 82,32% of the 28 days. The average number of recommended measurements taken was 61,80 (SD 36,05) corresponding to 55,18%. In the questionnaires, 95% answered that it was easy to learn how to use the device (answer 4 “I agree” or 5 “I totally agree”), 80% that it was easy to take BP measurements (4 or 5), 70% that they trusted the BP values (4 or 5), 100% that it was easy to telemonitor the data (4 or 5), 100% gave great importance to the doctor receiving constantly the data (4 or 5) and 70% preferred the Freescan® over cuff-based BP monitors. During the study, 7 cases of non-controlled hypertension and 3 cases with at least one suspected AF measurement were reported to the responsible physician. The number of recommended measurements taken was not influenced by age or sex. Conclusions: In this prospective study of hypertensive patients followed up in hypertension hospital consultation, most participants preferred Freescan® over cuffbased BP monitors and there was a good adaptation to the new technology as well as a good adherence to the number of measurements recommended independent of age or sex. That leads us to conclude that these new devices may have an important role in the follow-up of patients with hypertension, in order to increase control and decrease the mortality and morbidity associated with this condition.